Multiliteracies Project Approach: Dated or a Worthy Learning Tool? - Puteh-Behak, F; Ismail, IR (Penerbit Univ Kebangsaan Malaysia, 2024)
In the midst of the popularity of massive open online learning approach and the fourth industrial revolution, it seems that multiliteracies approach is losing its significance in the educational setting of Malaysia. This paper discusses the relevance of multiliteracies project approach in the current Malaysian academic arena since its introduction in the early 21st century. This paper will begin by outlining the significance of the multiliteracies approach at the local and global educational settings. The current study is part of a larger action research project that involved four action research cycles investigating multiliteracies approach in ESL (English for the Second Language) contexts. The data for the current study were collected from the second action research cycle, involving 28 participants who were learners of ESL at Bakti Polytechnic (pseudonym). Data were collected through classroom observation, semistructured interviews and classroom documents. The data show that multiliteracies approach still provides students with evocative learning experience and promotes the acquisition of necessary skills for students to participate in the 21st century particularly technological, critical thinking and teamwork skills. Findings suggest that multiliteracies approach has the potential to be expanded to further include the properties of the current sensation of the fourth industrial revolution.